1859 Wash. Sess. Laws 109, ch. 2, § 30 - (:unkn) unknown (My University, 1859)
Prohibited exhibiting, in a rude, angry, or threatening manner, a pistol, Bowie knife, or other dangerous weapon. Punishable by imprisonment up to 1 year and a fine up to $500.
Keywords: BRANDISHING